Comparison of intravitreal afl ibercept and ranibizumab for macular edema secondary to branch retinal vein occlusion - Kaya, Faruk; Koçak, İbrahim; Aydın, Ali; Baybora, Hakan; Koç, Hacı; Karabela, Yunus (Gazi Göz Vakfı, 2018)
Purpose: To compare the effi cacy of intravitreal injection of ranibizumab and afl ibercept on the treatment of macular edema due to branch retinal vein occlusion (BRVO). Materials and Methods: In this retrospective study; eyes with macular edema secondary to BRVO which treated with intravitreal ranibi- zumab (IVR) or afl ibercept( IVA) and followed at least 12 months between September 2012 and March 2016 were reviewed. Mean number of injections and changes in two groups’ best-corrected visual acuity (BCVA) and central macular thickness (CMT) measured by optical coherence tomography at month 1, 3, 6 and 12 were reviewed and compared. Results: Mean BCVA improved signifi cantly in IVR group (p=0.03, 0.04, 0.02 and 0.03 respectively) and IVA group (p=0.02, 0.04, 0.03 and 0.03 respectively ; and CMT decreased signifi cantly in IVR group (p=0.02, 0.02, 0.02 and 0.03 respectively) and IVA group (p=0.001, 0.03, 0.01 and 0.02 respectively) at 1, 3, 6 and 12th months. Mean number of injections per eye within twelve months were 3.4±1.2 in rani- bizumab group, and 2.2±1.1 in afl ibercept group (p=0.03). There were no signifi cant differences between two groups at month 12, including fi nal BCVA, changes in BCVA, fi nal CMT, and changes in CMT (p> 0.05) Conclusion: Afl ibercept presented similar decrease in CMT and improvement in BCVA with lesser number of injections for macular edema due to BRVO.

Amaç: Retina ven dal tıkanıklığına (RVDT) sekonder gelişen macula ödeminde intravitreal ranibizumab ve afl ibercept enjeksiyonunun etkinliğinin karşılaştırılması. Gereç ve Yöntemler: Retrospektif çalışmamızda Eylül 2012 ve Mart 2016 arasında RVDT’na sekonder gelişen macula ödemi için intra- vitreal ranibizumab (IVR) ve afl ibercept (IVA) enjeksiyonu uygulanmış ve az 12 ay takip edilmiş hastalar değerlendirildi Ortalama enjek- siyon sayısı, iki grup arasındaki 1,3,6 ve 12. aylarda ölçülenen en iyi düzeltilmiş görme keskinliği (EDGK) ve optic koherens tomografi de ölçülmüş santral maküler kalınlık (SMK) farkları değerlendirildi ve karşılaştırıldı. Bulgular: 1, 3, 6 ve 12. aylarda ortalama EDGK; IVR (sırasıyla p=0.03, 0.04, 0.02 ve 0.03) ve IVA grubunda (sırasıyla p=0.02, 0.04, 0.03 ve 0.03) anlamlı olarak artarken SMK; IVR (sırasıyla p=0.02, 0.02, 0.02 ve 0.03) ve IVA grubunda (sırasıyla p=0.001, 0.03, 0.01 ve 0.02) anlamlı olarak azaldı. 12 ay sonunda ortalama enjeksiyon sayısı ranibizumab grubunda 3.4±1.2, afl ibercept grubunda 2.2±1.1 oldu (p=0.03). 12 ay sonunda iki grup arasında son EDGK, EDGK değişimi, son SMK ve SMK değişimi açısından anlamlı fark yoktu (p> 0.05). Sonuç: RVDT’na bağlı macula ödeminde afl ibercept daha az enjeksiyon sayısı ile ranibizumaba benzer şekilde SMK’da azalma ve ED- GK’da artış sunmuştur.
Retina ven dal tıkanıklığına sekonder gelişen makula ödeminde intravitreal afl ibercept ve ranibizumab karşılaştırması
Keywords: Branch Retinal Vein; Macular Edema; Intravitreal Afl Ibercept; Retina Ven Dalı; Macula Ödemi; İntravitreal Aflibercept